Factors leading to excessive fatigue in nurses - a three-year follow-up study - Stand Hiestand; Siri Waage; Ingeborg Forthun; Ståle Pallesen; Bjørn Bjorvatn (BMC, 2024)
Abstract Background Global nursing shortages necessitate the identification of mitigatable factors that may reduce nursing absence and turnover. Fatigue has been shown to be associated with these issues. This study aimed to identify factors leading to development of or recovery from excessive fatigue in nurses as these can offer actionable avenues for protecting nurses against fatigue or supporting fatigue recovery. Methods A longitudinal study among nurses randomly sampled from the Norwegian Nurse's Organization. The Chalder Fatigue Questionnaire measured fatigue. Dichotomized scoring was used, with scores ≥ 4 considered excessive fatigue. The study included questions on shift work schedules, psychosocial work characteristics, sleep, body mass index, physical activity, caffeine, alcohol, mental health, etc. Two sets of logistic regression analysis were conducted (one for development of and one for recovery from excessive fatigue), evaluating how changes in work, lifestyle and health between baseline (2015) and follow-up (2018) affected first, odds of development of excessive fatigue and second, odds of recovery from excessive fatigue. Results Among 1,311 included nurses, 21.6% maintained, 13.3% developed, and 18.0% recovered from excessive fatigue (2015-2018). Within work characteristics, increased psychological work demands were associated with development of excessive fatigue OR = 1.77 (CI = 1.11-2.82). Several work characteristics were associated with recovery from excessive fatigue, including decreased decision latitude (OR = 0.39; CI = 0.19-0.82) and increased coworker support (OR = 1.90; CI = 1.11-3.24). Shift work variables were not associated with fatigue outcomes. Amongst lifestyle factors, changes in sleep duration, obesity, and exercise were significant. Notably, developing inappropriate sleep duration (OR = 2.84; CI = 1.47-5.48) increased odds of developing excessive fatigue, while maintaining inappropriate sleep duration (< 6 h or > 8 h) (OR = 0.19; CI = 0.54-0.65) decreased odds of recovering. All assessed health conditions (depression, anxiety, insomnia, and shift work disorder) were related to development of (ORs 2.10-8.07) or recovery from (ORs 0.10-0.50) excessive fatigue. Depression, for example, increased odds of development of (OR = 8.07; CI = 2.35-27.66) and decreased odds of recovery (OR = 0.10; CI = 0.04-0.26) from excessive fatigue. Conclusions Changes in lifestyle factors, health conditions, and psychosocial work factors were associated with development of and recovery from excessive fatigue. Sleep and psychosocial work factors played important roles. We found no relationship with shift work schedules.